Quality over Quantity: A Lineage-Survival Strategy of Elite Families in Premodern Korea - Lee, Sangkuk; Park, Jong Hee (Social Science History, 2019)
In this article, we study social mobility across multiple generations in premodern Korea. Using two extant oldest family records, jokbo, we construct a prospective genealogical microdata containing the entire records of public offices and reproduction over five generations of the two elite family lineages in premodern Korea. We argue that the confluence of an ambiguous stratification system with a limited number of high-ranking offices generated a trade-off for parents between the quantity and quality of positions attained by their offspring. The result of the trade-off was unequal distributions of mobility-related family resources to maximize the lineage's collective goal, rather than to maximize individual children's social ranks. Using a novel empirical strategy to consider the heterogeneous resource-allocation within elite families, we present empirical evidence on associations between parents' and grandparents' social ranks and quality of offices achieved by children of elite Korean families.